Analysis of Patient Satisfaction on Healthcare Service with Potential Gain in Customer Value (PGCV) Method (Case Study: Children’s Poly Service at Puskesmas Simpang IV Sipin Kota Jambi) - Isti Mardiani; Daumi Rahmatika; Alya Triska Sutrisno; Asfia Fitri Aras (Management Department, Faculty of Economics and Business, Universitas Jambi, 2023)
Puskesmas Simpang IV Sipin Jambi still continuing to improve customer satisfaction. One indicator of the success of health services in Puskesmas is patient satisfaction. After observation, the reality of services at the puskesmas still does not meet customer expectations. This is because the Puskesmas has not prioritized what services need to be repaired and improved. This study uses the Potential Gain in Customer Value (PGCV) method to find out the description of the service desired by the customer. This research is a quantitative descriptive research. The data taken was carried out by distributing online questionnaires to 120 respondents. The results of the PGCV analysis show that the Responsiveness attribute (3,277) and the two Tangible attributes (2,447), (2,188) become 3 priority focuses in improving service quality.